Genome-wide association mapping for salinity recovery of rice seedlings grown in hydroponic and field conditions - Siddique, Md. Abubakar; De Ocampo, Marjorie; Bagunu, Efren; Quick, William Paul; Diaz, Maria Genaleen; Henry, Amelia (Royal Society, 2025)
"Salinity stress significantly impacts global food production by hindering crop growth and reducing cultivable land. Efforts to develop salinity-tolerant rice varieties have faced challenges due to the complexity of salinity tolerance traits and a lack of suitable genetic donors. One complexity of salinity stress is that fluctuating degrees of severity often occur over a rice growing season, which may require plants to recover quickly as salinity levels temporarily decrease. This study evaluated salinity recovery in 256 diverse rice accessions, including 230 from the 3K Rice Genomes Project. Key physiological traits were measured, indicating accessions that outperformed the salinity-tolerant variety FL478, three of which were common in both the field and in hydroponics: BRRI dhan 47, Kalar Kar and WAS 170-B-B-1-1. Genome-wide association mapping identified significant single nucleotide polymorphisms linked to salinity tolerance and recovery-related traits, with four genes (LOC_Os01g71350, LOC_Os02g56510, LOC_Os03g53150 and LOC_Os04g40410) consistently identified in both the field and greenhouse. Based on colocating loci, a favourable haplotype for salinity recovery was identified on chr 3. The accessions with salinity tolerance and good recovery and the genes/loci identified here will provide useful information for future studies on genetics and breeding of salt tolerant/resilient rice. This article is part of the theme issue ‘Crops under stress: can we mitigate the impacts of climate change on agriculture and launch the ‘Resilience Revolution’?’